High-entropy hydrotalcite nanosheet as well as preparation method and application thereof

Through the preparation and application of high-entropy hydrotalcite nanosheets, the problems of drug resistance, non-specific diffusion and toxic side effects in existing tumor treatment methods have been solved, and efficient tumor targeted therapy and improvement of nuclear magnetic imaging effects have been achieved.

CN119326883APending Publication Date: 2025-01-21TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310880095.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing tumor treatment methods have problems such as drug resistance, nonspecific systemic spread, too low drug concentration and major toxic side effects, which are difficult to effectively improve the therapeutic effect while reducing damage to normal cells.

Method used

High-entropy hydrotalcite nanosheets are used, and the layers contain metal ions such as Cu, Mn, Co, Ni and Fe. The nanosheets are synthesized through a simple preparation method and applied to sonosensitizers. Ultrasonic activation is used to generate a large amount of Reactive oxygen species to achieve targeted therapy of tumors.

Benefits of technology

High-entropy hydrotalcite nanosheets generate a large amount of reactive oxygen species in the tumor microenvironment after ultrasound, which significantly improves the effect of sonodynamic therapy. At the same time, due to the presence of manganese ions, the nuclear magnetic imaging effect is improved and has good biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326883A_ABST
    Figure CN119326883A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy hydrotalcite nanosheet as well as a preparation method and application thereof. Metal in a laminate of the high-entropy hydrotalcite nanosheet comprises Cu, Mn, Co, Ni and Fe, and all the metal exist in the form of ions. The surface of the laminate has positive charges, and the interlayer of the laminate has negative charges; and the size of the hydrotalcite nanosheet is 30 + / -10nm. When the high-entropy hydrotalcite nanosheet is used as a sound-sensitive agent, the high-entropy hydrotalcite nanosheet has nuclear magnetic imaging performance, can generate a large number of active oxygen species in a tumor microenvironment after ultrasonic treatment, and shows an excellent sonodynamic therapy effect. In addition, manganese ions in the hydrotalcite nanosheet can effectively improve the nuclear magnetic imaging effect, and the biocompatibility is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tumor drug preparation, and more specifically to a high-entropy hydrotalcite nanosheet and a preparation method and application thereof. Background Art

[0002] According to the latest report on cancer released by the World Health Organization, one in six people dies from cancer. Currently, the methods for treating cancer include surgery, chemotherapy, radiotherapy, immunotherapy, targeted therapy and other therapies (Int. J. Mol. Sci. 2022, 23, 2288.). Since the invention of anesthesia in 1846, surgical treatment has played an important role in removing malignant tumors in the body, but surgical resection of tumor tissue has the disadvantage of easy recurrence (Materials Science & Engineering C 108 (2020) 110198). Chemotherapy is often used in combination with one or more other drugs to kill cancer cells. Drugs can circulate to most tissues and organs throughout the body for systemic treatment. However, chemotherapy also has some defects, such as easy drug resistance, nonspecific systemic diffusion of anti-tumor drugs, too low drug concentration reaching the target tissue, and large toxic side effects. These defects affect the proliferation of normal cells and damage normal tissues and organs of the human body. Radiotherapy is one of the main ways to treat tumors in clinical practice. It destroys cancer cells by generating local ionizing radiation to achieve anti-tumor effects. Radiotherapy is very important for patients who cannot undergo surgery or have incompletely removed tumors and patients with recurrent tumors. Radiotherapy can induce immunogenic cell death, thereby inducing systemic immune effects. However, radiotherapy can cause radiation damage to adjacent normal tissues. In addition, tumors have a certain resistance to radiotherapy, which limits the therapeutic effect of radiotherapy (Proc Natl Acad Sci USA, 2019, 116(37): 18584-9.). Therefore, it is necessary to find a treatment strategy that can both improve the treatment effect of tumors and reduce damage to normal cells.

[0003] Since the late 1980s, sonodynamic therapy using low-intensity ultrasound and sonosensitizers has become a new cancer treatment. Ultrasound can reach deep organs such as the liver, pancreas, and tumors. And ultrasound is a mechanical sound wave that can be precisely focused on the tumor site to achieve targeted activation of sonosensitizers, thereby achieving selective killing of cancer cells without damaging surrounding healthy organs. Sonodynamic therapy produces ROS through a combination of low-intensity ultrasound, O2, and sonosensitizers, causing cancer cell apoptosis, and both ultrasound and sonosensitizers are non-toxic and harmless to normal tissues (Chem.Soc.Rev.2020,49,3244-3261). Sonodynamic therapy has the advantages of being non-invasive and low-cost, and is a promising cancer treatment method.

[0004] Based on this, it is necessary to provide a simple method for preparing high-entropy hydrotalcite nanosheet materials so that the material can be used in tumor treatment. Summary of the invention

[0005] Based on the above facts, the object of the present invention is to provide a high-entropy hydrotalcite nanosheet and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] On the one hand, the present invention provides a high-entropy hydrotalcite nanosheet, wherein the metals in the layer plates of the hydrotalcite nanosheet include Cu, Mn, Co, Ni and Fe, and each metal exists in the form of ions; the surface of the layer plates has a positive charge and the interlayers have a negative charge; and the size of the hydrotalcite nanosheet is 30±10nm.

[0008] It should be noted that the "size" in the technical solution of the present invention refers to the length of the nanosheet.

[0009] In the high entropy hydrotalcite nanosheet of the technical solution, the layer plate contains metal ions such as Cu, Mn, Co, Ni and Fe at the same time, and these metal ions are evenly distributed in the layer plate. Compared with NiFe-hydrotalcite nanosheet, the high entropy hydrotalcite nanosheet has a stronger ability to generate active oxygen. Furthermore, the molar ratio of Cu, Mn, Co, Ni and Fe is 1:1:1:1:1.

[0010] In another aspect, the present invention provides a method for preparing the high entropy hydrotalcite nanosheets as described above, comprising the following steps:

[0011] The soluble salt solution of the metal and the aqueous solution of sodium hydroxide are added to a 0.2 mol / L sodium nitrate solution at the same time, the pH is adjusted to alkaline, and the mixture is stirred and reacted at 50-100° C. for 0.5-6 hours, and then centrifuged, washed and dried to obtain the high entropy hydrotalcite nanosheets.

[0012] The obtained high entropy hydrotalcite nanosheets are dispersed in water to obtain hydrotalcite nanosheet colloids.

[0013] By controlling the stirring reaction temperature, the size of the obtained hydrotalcite nanosheets can be uniform and small.

[0014] Furthermore, in the soluble metal salt solution, the soluble metal salt is a nitrate of the metal or a soluble chloride of the metal.

[0015] Furthermore, the soluble salt of the metal consists of copper nitrate, manganese chloride, cobalt nitrate, nickel nitrate and iron nitrate.

[0016] Furthermore, the soluble salt solution of the metal is composed of an aqueous solution of copper nitrate, an aqueous solution of manganese chloride, an aqueous solution of cobalt nitrate, an aqueous solution of nickel nitrate and an aqueous solution of iron nitrate.

[0017] Furthermore, the concentrations of the aqueous solution of copper nitrate, the aqueous solution of manganese chloride, the aqueous solution of cobalt nitrate, the aqueous solution of nickel nitrate and the aqueous solution of iron nitrate are all 0.04 mol / L.

[0018] Furthermore, in the soluble salt solution of the metal, the molar ratio of copper nitrate, manganese chloride, cobalt nitrate, nickel nitrate and iron nitrate is 1:1:1:1:1.

[0019] Furthermore, in the sodium nitrate solution, the solvent is a mixture of polyethylene glycol 400 and water in a volume ratio of 1:3.

[0020] In another aspect, the present invention provides a sonosensitizer prepared from the high entropy hydrotalcite nanosheets as described above.

[0021] In another aspect, the present invention provides use of the high entropy hydrotalcite nanosheets as described above in the preparation of sonosensitizers for tumor treatment.

[0022] In another aspect, the present invention provides use of the high entropy hydrotalcite nanosheets described above in the preparation of a magnetic resonance imaging agent.

[0023] Unless otherwise specified, various raw materials used in the present invention can be purchased commercially or obtained by conventional means in the art.

[0024] The beneficial effects of the present invention are as follows:

[0025] The high entropy hydrotalcite nanosheet provided by the present invention has nuclear magnetic resonance imaging performance when used as a sonosensitizer. After ultrasound, a large amount of reactive oxygen species can be generated in the tumor microenvironment, showing an excellent sonodynamic therapy effect. In addition, the manganese ions in the hydrotalcite nanosheet can effectively improve the nuclear magnetic resonance imaging effect and have good biocompatibility.

[0026] In the preparation method of the high entropy hydrotalcite nanosheet provided by the invention, the copper-manganese-cobalt-nickel-iron hydrotalcite nanosheet is synthesized by a double-drop template method. The preparation method is simple and the conditions are controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0028] Figure 1 The transmission electron microscope image of the high entropy hydrotalcite nanosheets prepared in Example 1 is shown.

[0029] Figure 2The X-ray diffraction pattern of the high entropy hydrotalcite nanosheets prepared in Example 1 is shown.

[0030] Figure 3 The electron spin resonance images of the high entropy hydrotalcite nanosheets prepared in Example 1 showing the generation of three types of active oxygen.

[0031] Figure 4 The UV images of the high entropy hydrotalcite nanosheets prepared in Example 1 before and after ultrasound generation of active oxygen are shown. DETAILED DESCRIPTION

[0032] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0033] Example 1

[0034] A preparation method of high entropy hydrotalcite nanosheets comprises the following steps:

[0035] 1) Dissolve 0.79g of manganese chloride tetrahydrate, 1.62g of ferric nitrate nonahydrate, 1.16g of cobalt nitrate hexahydrate, 1.16g of nickel nitrate hexahydrate and 0.97g of copper nitrate trihydrate in 100mL of water and mix them evenly to obtain liquid A; dissolve 1.70g of sodium nitrate in 25ml of polyethylene glycol 400 and 75ml of water and mix them evenly to obtain liquid B; dissolve 2.0g of sodium hydroxide in 100ml of water and mix them evenly to obtain liquid C; under stirring in a water bath at 80°C, slowly add liquid A and liquid C to liquid B at the same time, adjust the pH to 9, react for 0.5h, centrifuge, wash, freeze-dry, and disperse in water to obtain high entropy hydrotalcite nanosheets (CuNiCoMnFe-LDH) colloid.

[0036] In this example, the transmission electron microscope image of the prepared high entropy hydrotalcite nanosheets is as follows: Figure 1 shown. Figure 1 The high entropy hydrotalcite is uniform in size, with a size of 30 ± 10 nm. Figure 2 This is the X-ray diffraction pattern of high entropy hydrotalcite nanosheets. Figure 3 It was shown by electron paramagnetic resonance spectroscopy that the high entropy material exhibited three types of active oxygen generation capabilities. Figure 4 It is shown that the ability of high entropy hydrotalcite to generate active oxygen is 1.65 times that of NiFe-LDH (Comparative Example 4) through UV test, and the ability of high entropy hydrotalcite to generate active oxygen after ultrasound is 1.28 times that before ultrasound.

[0037] Example 2

[0038] A preparation method of a high entropy hydrotalcite nanosheet material comprises the following steps:

[0039] 1) Dissolve 0.79g of manganese chloride tetrahydrate, 1.62g of ferric nitrate nonahydrate, 1.16g of cobalt nitrate hexahydrate, 1.16g of nickel nitrate hexahydrate and 0.97g of copper nitrate trihydrate in 100mL of water and mix them evenly to obtain liquid A; dissolve 1.70g of sodium nitrate in 100ml of water containing 25% formamide and mix them evenly to obtain liquid B; dissolve 2.0g of sodium hydroxide in 100ml of water and mix them evenly to obtain liquid C; while stirring in a water bath at 80°C, slowly add liquid A and liquid C to liquid B at the same time, adjust the pH to 9, react for 0.5h, centrifuge, wash, freeze-dry, and disperse in water to obtain hydrotalcite nanosheet colloid.

[0040] The obtained high entropy hydrotalcite nanosheet material has a nanosheet size of about 30±10 nm. When dispersed in water, the hydrotalcite material exhibits good performance in generating ROS.

[0041] Example 3

[0042] A preparation method of a high entropy hydrotalcite nanosheet material comprises the following steps:

[0043] 1) Dissolve 0.79g of manganese chloride tetrahydrate, 1.62g of ferric nitrate nonahydrate, 1.16g of cobalt nitrate hexahydrate, 1.16g of nickel nitrate hexahydrate and 0.97g of copper nitrate trihydrate in 100mL of water and mix them evenly to obtain liquid A; dissolve 1.70g of sodium nitrate in 100mL of water containing 25% formamide and mix them evenly to obtain liquid B; dissolve 2.0g of sodium hydroxide in 100mL of water and mix them evenly to obtain liquid C; while stirring in a water bath at 50°C, slowly add liquid A and liquid C to liquid B at the same time, adjust the pH to 9, react for 3h, centrifuge, wash, freeze-dry and disperse in water to obtain hydrotalcite nanosheet colloid.

[0044] The obtained high entropy hydrotalcite nanosheet material has a nanosheet size of about 30±10 nm. When dispersed in water, the hydrotalcite material exhibits good performance in generating ROS.

[0045] Example 4

[0046] Example 1 was repeated, except that the step 1) "1.70 g of sodium nitrate was dissolved in 100 ml of water containing 25% polyethylene glycol" was replaced with "1.70 g of sodium nitrate was dissolved in 100 ml of water containing 25% chitosan". The other conditions remained unchanged, and a high entropy hydrotalcite nanosheet material was prepared. The size of the obtained hydrotalcite material was about 30 ± 10 nm, and it was dispersed in water. The hydrotalcite material showed good performance in generating ROS.

[0047] Example 5

[0048] Example 1 was repeated, except that the step 1) "1.70 g of sodium nitrate was dissolved in 100 ml of water containing 25% polyethylene glycol" was replaced with "1.70 g of sodium nitrate was dissolved in 100 ml of water containing 15% cellulose". The other conditions remained unchanged, and a high entropy hydrotalcite nanosheet material was prepared. The size of the obtained hydrotalcite material was about 30 ± 10 nm, and it was dispersed in water. The hydrotalcite material showed good performance in generating ROS.

[0049] Example 6

[0050] Example 1 was repeated, except that the step 1) "dissolving 1.70 g of sodium nitrate in 100 ml of water containing 25% polyethylene glycol" was replaced with "dissolving 0.034 g of sodium nitrate in 100 ml of water containing 25% Tween". The other conditions remained unchanged, and a high entropy hydrotalcite nanosheet material was prepared. The size of the obtained hydrotalcite material was about 30 ± 10 nm, and it was dispersed in water. The hydrotalcite material showed good performance in generating ROS.

[0051] Example 7

[0052] Example 1 was repeated, except that "stirring in a water bath at 80°C" in step 1) was replaced with "stirring in a water bath at 50°C". The other conditions remained unchanged, and a high entropy hydrotalcite nanosheet material was prepared. The size of the obtained hydrotalcite material was about 30±10nm, and it was dispersed in water. The hydrotalcite material showed good performance in generating ROS.

[0053] Example 8

[0054] Example 2 was repeated, except that "stirring in a water bath at 80°C" in step 1) was replaced with "stirring in a water bath at 70°C". "Reacting for 0.5h" in step 1) was replaced with "reacting for 3h". The other conditions remained unchanged, and a high-entropy hydrotalcite nanosheet material was prepared. The size of the obtained hydrotalcite material was about 30±10nm, and it was dispersed in water. The hydrotalcite material showed good performance in generating ROS.

[0055] Example 9

[0056] Example 2 was repeated, except that "stirring in a water bath at 80°C" in step 1) was replaced with "stirring in a water bath at 60°C". "Reacting for 0.5h" in step 1) was replaced with "reacting for 5h". The other conditions remained unchanged, and a high-entropy hydrotalcite nanosheet material was prepared. The size of the obtained hydrotalcite material was about 30±10nm, and it was dispersed in water. The hydrotalcite material showed good performance in generating ROS.

[0057] Example 10

[0058] Example 2 was repeated, except that "stirring in a water bath at 80°C" in step 1) was replaced with "stirring in a water bath at 50°C". "Stirring for 0.5h" was replaced with "stirring for 6h". The other conditions remained unchanged, and a high-entropy hydrotalcite nanosheet material was prepared. The obtained hydrotalcite material had a large size of about 30±10nm, and when dispersed in water, the hydrotalcite material showed good performance in generating ROS.

[0059] Comparative Example 1

[0060] The preparation method is basically the same as that in Example 1, except that the "aqueous solution containing 25% polyethylene glycol" in 1) is replaced with "aqueous solution" and the other conditions remain unchanged. No 30±10 nm high entropy hydrotalcite nanosheets are obtained.

[0061] Comparative Example 2

[0062] The preparation method is basically the same as that in Example 1, except that the "PH controlled at 9" in 1) is replaced by "PH controlled at 7", and the other conditions remain unchanged, and no high entropy hydrotalcite nanosheets are obtained.

[0063] Comparative Example 3

[0064] The preparation method is basically the same as that in Example 1, except that "stirring in a water bath at 80°C" in 1) is replaced by "stirring in a water bath at 0°C", and the other conditions remain unchanged, and no high entropy hydrotalcite nanosheet material is obtained.

[0065] Comparative Example 4

[0066] The preparation method of hydrotalcite nanosheets is basically the same as that of Example 1, except that the step "0.79 g of manganese chloride tetrahydrate, 1.62 g of ferric nitrate nonahydrate, 1.16 g of cobalt nitrate hexahydrate, 1.16 g of nickel nitrate hexahydrate and 0.97 g of copper nitrate trihydrate are dissolved in 100 mL of water and mixed to form liquid A" in 1) is replaced with "1.62 g of ferric nitrate nonahydrate and 1.16 g of nickel nitrate hexahydrate are dissolved in 100 mL of water and mixed to form liquid A", and the other conditions remain unchanged, and NiFe-LDH is obtained, but no high-entropy hydrotalcite nanosheet material is obtained. Figure 4 It is shown that the ability of the hydrotalcite nanosheets to generate active oxygen is much lower than that of the high entropy hydrotalcite nanosheets prepared in Example 1 through ultraviolet testing.

[0067] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A high entropy hydrotalcite nanosheet, characterized in that: The metals in the layer plates of the hydrotalcite nanosheets include Cu, Mn, Co, Ni and Fe, and each metal exists in the form of ions; the surface of the layer plates has positive charges, and the interlayers have negative charges; and the size of the hydrotalcite nanosheets is 30±10 nm.

2. The high entropy hydrotalcite nanosheet according to claim 1, characterized in that: The molar ratio of Cu, Mn, Co, Ni and Fe is 1:1:1:1:

1.

3. The method for preparing the high entropy hydrotalcite nanosheets according to any one of claims 1 to 2, characterized in that: The steps include: The soluble salt solution of the metal and the aqueous solution of sodium hydroxide are added to a 0.2 mol / L sodium nitrate solution at the same time, the pH is adjusted to alkaline, and the mixture is stirred and reacted at 50-100° C. for 0.5-6 hours, and then centrifuged, washed and dried to obtain the high entropy hydrotalcite nanosheets.

4. The preparation method according to claim 3, characterized in that: In the soluble metal salt solution, the soluble metal salt is a nitrate of the metal or a soluble chloride of the metal.

5. The preparation method according to claim 4, characterized in that: The soluble salts of the metals consist of copper nitrate, manganese chloride, cobalt nitrate, nickel nitrate and iron nitrate.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the copper nitrate, manganese chloride, cobalt nitrate, nickel nitrate and iron nitrate is 1:1:1:1:

1.

7. The preparation method according to claim 3, characterized in that: In the sodium nitrate solution, the solvent is a mixture of polyethylene glycol 400 and water in a volume ratio of 1:

3.

8. A sonosensitizer, characterized in that: The method is prepared from the high-entropy hydrotalcite nanosheets as described in any one of claims 1 to 2.

9. Use of the high entropy hydrotalcite nanosheets according to any one of claims 1 to 2 in the preparation of sonosensitizers for tumor treatment.

10. Use of the high entropy hydrotalcite nanosheets according to any one of claims 1 to 2 in the preparation of a magnetic resonance imaging agent.

Citation Information

Cited By

  • Preparation method and application of multienzyme mimic activity NiFeMnCu-LDH

    CN120241787A

  • Five-element co-doped porous CoFeCuMnNi-LDH nano material as well as preparation method and application thereof

    CN121819864A